2018
DOI: 10.2166/wst.2018.308
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cu2+ and mechanism by natural biofilm

Abstract: The biofilm culturing device fixed on the slides was vertically placed in the commonly called small Li Lake of Jiangnan University. The adsorption experiment of Cu2+ was carried out by mature biofilm. Besides, scanning electron microscope (SEM), polymerase chain reaction and denaturing gradient gel electrophoresis (PCR-DGGE), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy-energy spectrum (SEM-EDX) were used to analysis the effect of Cu2+ on the morphological structure of biofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…92 For instance, Cu +2 adsorption in biofilms was shown to result in the binding of Cu +2 with the hydroxyl groups and amide groups present in the extracellular polymeric substances found in the biofilms. 93 This suggests that metal ions can be used as a nutrient by the organisms in the biofilms to maintain a sustainable, nutrient-rich environment within the biofilms through both ion adsorption and desorption. However, the adsorption and complexation reactions involving toxic metals such as Pb are known to be governed by the tolerance potential of microorganisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…92 For instance, Cu +2 adsorption in biofilms was shown to result in the binding of Cu +2 with the hydroxyl groups and amide groups present in the extracellular polymeric substances found in the biofilms. 93 This suggests that metal ions can be used as a nutrient by the organisms in the biofilms to maintain a sustainable, nutrient-rich environment within the biofilms through both ion adsorption and desorption. However, the adsorption and complexation reactions involving toxic metals such as Pb are known to be governed by the tolerance potential of microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…Ion exchange has been discussed in the literature as the major mechanism of metal ion adsorption in biofilms . For instance, Cu +2 adsorption in biofilms was shown to result in the binding of Cu +2 with the hydroxyl groups and amide groups present in the extracellular polymeric substances found in the biofilms . This suggests that metal ions can be used as a nutrient by the organisms in the biofilms to maintain a sustainable, nutrient-rich environment within the biofilms through both ion adsorption and desorption.…”
Section: Resultsmentioning
confidence: 99%
“…Duong et al, 2010; Morin et al, 2008), Zn (e.g. Arini et al, 2011), and Cu (Cheng et al, 2018) are accumulated by periphytic biofilms and by sulfate-reducing bacterial biofilms (Cu; White and Gadd, 2000). All of these biofilms are present in Lake Uru Uru (Guédron et al, 2017) and may affect the shallow vertical distribution of elements in this aqueous system.…”
Section: Discussionmentioning
confidence: 99%
“…This results indicated that biofilms might accumulate the Cr(VI) from the surrounding waters [16]. Biofilms in the aquatic ecosystems have been reported to have the ability to attract and reserve ions including heavy metal ions such as Cr(VI) (Kurniawan, 2015;Cheng, et al, 2018, Julien, et al, 2014.…”
Section: Cr(vi) Concentration In the Biofilm And The Surrounding Watermentioning
confidence: 99%